Review of Transport Tariff at Ferry Port on Track Kariangau– Penajam, East Kalimantan Province - Windi Nopriyanto; Sri Kartini; Deska Uliyani (IWTJ : International Water Transport Journal, 2019)
The Ferry Port is located in the Village Kariangau with geographical location 116˚ 49 '2.852 "E - 116˚ 49' 15.2800" E and 1˚ 12 '1.188 "LS - 1˚ 12' 12.046" LS. This port serves 3 commercial track, one track Kariangau - Penajam served by 17 vessels from 6 shipping company. In operating facilities and infrastructure to organize the crossing transport, Shipping Company issued vessel operating expenses adjusted for operational trip the ship every day. Operational costs can influence the changes in the condition of transport fares. Transport Tariff at the Kariangau Ferry Port set by East Kalimantan Governor Decree number 45 of 2017. The trip vessel operating expenses amounted to 4,293,355 with a profit based on applicable tariff amounted 2,505,908.29. Based on the analysis, the tariff for passengers by 9567 / trip and profit at the rate of 3,723,823 results analysis / trip accordance Load Factor analysis today is 49.23%, then, there should be a review of implementation in the Port Kariangau Tariff that could affect the operators' revenue and the condition of the Port Load Factor.